Dose-dependent effects of mandibular advancement on upper airway collapsibility and muscle function in obstructive sleep apnea. Issue 6 (21st February 2019) - Bamagoos, Ahmad A; Cistulli, Peter A; Sutherland, Kate; Ngiam, Joachim; Burke, Peter G R; Bilston, Lynne E; Butler, Jane E; Eckert, Danny J
Abstract: Study Objectives: Mandibular advancement splints (MAS) are the leading treatment alternative to continuous positive airway pressure (CPAP) for obstructive sleep apnea (OSA). However, not all patients experience clinical benefit and treatment prediction remains challenging. Understanding the effects of mandibular advancement on pharyngeal collapsibility and muscle function may provide valuable information on the mechanisms of MAS, and thereby help to develop novel approaches for patient selection. Thus, we aimed to determine dose-dependent effects of mandibular advancement on pharyngeal collapsibility and muscle function concurrently in OSA patients undergoing MAS therapy. Methods: Twelve (11 male) MAS-naïve patients underwent a detailed physiology sleep study (polysomnography) to quantify pharyngeal collapsibility (PCRIT ), pharyngeal muscle responsiveness to negative pharyngeal pressure (via genioglossus intramuscular electromyography and an epiglottic pressure sensor) and effectiveness to restore airflow and minute ventilation (Vi) after 1-minute transient CPAP reductions (induced airflow-limitation) at three mandibular advancement positions: 0% (habitual bite), 50% and 100% of the maximum comfortable mandibular advancement. Standard clinical polysomnography after MAS therapy optimization was performed to determine treatment outcome. Results: Overall, participants were obese with severe OSA (mean ± SD : BMI = 31 ± 4 kg/m 2, apnea-hypopnea index [AHI] = 33 ± 14 events/hour). PCRIT decreased with mandibular advancement in a dose-dependent manner (1.8 ± 3.9 vs. −0.9 ± 2.9 vs. −4.0 ± 3.6 cmH2 O; p < 0.001). There was no systematic change in genioglossus muscle responsiveness ( p = 0.09) or effectiveness to restore peak airflow ( p = 0.4) or Vi ( p = 0.7) with mandibular advancement. Conclusions: Mandibular advancement reduces pharyngeal collapsibility in a dose-dependent manner without systematically changing genioglossus muscle function in a predominantly obese and severe OSA population. This indicates that the primary mode of action of MAS therapy is via improvement in passive pharyngeal anatomy.